Risk factors of tuberculosis in children with adult household tuberculosis contact - Setyoningrum, Retno Asih; Maharani, Rizky Arisanti; Hapsari, Rika; Chafid, Arda Pratama Putra (Paediatrica Indonesiana, 2024)
Background Since children are more likely than adults to become infected with Mycobacterium tuberculosis or suffer from tuberculosis (TB), it is important to identify the risk factors of TB in children with adult household TB contacts. Objective To identify the risk factors of TB in children with adult household TB contacts. Methods This cross-sectional study was conducted at the Pediatric Respirology Inpatient Ward and Outpatient Clinic at Dr. Soetomo Hospital, Surabaya, Indonesia, using medical records of hospitalized patients from 2010 to 2018. Patients were children below 18 years of age who had a history of adult TB household contact(s). We analyzed age at TB diagnosis, nutritional status, BCG vaccination status, and HIV status as possible risk factors of TB. Results A total of 367 children with adult household TB contacts were included in our study. Age of <5 years (OR 8.38; 95%CI 3.78 to 18.21; P<0.001), severe malnutrition (OR 8.88; 95%CI 1.19 to 66.27, P<0.05), absence of BCG scar (OR 2.96; 95%CI 1.32 to 6.62, P<0.05), and positive HIV status (OR 6.72; 95%CI 1.72-38.49, P<0.05) were risk factors for contracting active TB. Conclusion Age of <5 years, severe malnutrition, absence of BCG scar, and positive HIV status are significant risk factors for active TB in children with adult household TB contacts.